Livestock Assets Ownership Dynamics and Food Security in Wa West District in the Upper West Region of Ghana - Fuseini Nadi; Fred Nimoh; Ernestina Fredua Antoh; Richmond Anaman (Cita Konsultindo Research Center, 2022)
Rural households keep multiple livestock species across various income levels, and the sources of these animals differ. The study examined the dynamics in acquiring livestock assets and food security using a focus group discussion and cross-sectional survey of 400 households. Descriptive statistics and paired differences were employed to achieve the objectives. The results showed that livestock assets ownership within a household were mainly held as separate marital property. The ownership pattern indicated that men owned 81.3% of livestock assets while women held 14.9%, with 3.9% of livestock assets being jointly held by men and women. Also, livestock assets are acquired through inheritance, market purchases, NGO/Government and gifts. Women had limited opportunities in acquiring livestock compared to men due to discriminatory customary norms on inheritance. The paired difference in percentages of women’s and men’s total livestock proceeds spent on household food was significant, with women spending a higher fraction of their income on household food than men. Furthermore, the paired difference in the percentage of joint livestock income spent on food was higher than men. The study recommends that programmes target women’s economic empowerment to bridge the gender livestock assets gap to help improve the wellbeing of households.